Developing The Mathematics Learning Strategy Book For Blind Students In Junior High School - Enggar Prasetyawan; Lisda Fitriana Masitoh (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2019)
Blind students who do not have intellectual disabilities should study in inclusive schools. This is because they are the same as regular students who are able to learn and construct learning experiences well. They must get the best learning facilities to be successful. The purpose of this study was to produce a mathematics learning strategy book for blind students in junior high school. This book contains a general description of the characteristics of blind students, how to teach mathematics to blind students and class management strategies. This study is categorized as research and development. Development model in this study was adapted from Borg & Gall. The research instruments were  validation sheets, questionnaire assessment for teachers and questionnaire assessment for students. . Data analysis was done by converting the quantitative data into qualitative data in the form specified categories. This research resulted a mathematics learning strategy book for blind students in junior high school that proper to use because the book is valid and practical